STROMAL (MESENCHYMAL) TUMORS OF THE GASTROINTESTINAL TRACT: A CASE SERIES - Ahmed, Ijaz; Haleem, Abid; Jan, Attaullah (Journal of Postgraduate Medical Institute, 2011)
This is a case series of four patients, two males and two females between 40-60 years of age. These patients presented to our unit with variable symptoms during the past 3 years. Postoperative histopathology reports suggested these masses to be mesenchymal tumors of gut origin.